2020
DOI: 10.1007/s10877-020-00481-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of stretchable and wearable inkjet-printed strain gauge sensor for respiratory rate monitoring at different measurements locations

Abstract: Introduction: The respiration rate (RR) is a vital sign in physiological measurement and clinical diagnosis. RR can be measured using stretchable and wearable strain gauge sensors which detect the respiratory movements in the abdomen or thorax areas caused by volumetric changes. In different body locations, the accuracy of RR detection might differ due to different respiratory movement amplitudes. Few studies have quantitatively investigated the effect of the measurement location on the accuracy of new sensors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…[17] Another study evaluating the accuracy of a stretch sensor in measuring respiratory rate demonstrated differences between the site of measurement such as umbilicus, upper abdomen, xiphoid process and upper thorax with the largest error of 1.05 to −0.90 breaths/min in the upper abdomen. [18]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Another study evaluating the accuracy of a stretch sensor in measuring respiratory rate demonstrated differences between the site of measurement such as umbilicus, upper abdomen, xiphoid process and upper thorax with the largest error of 1.05 to −0.90 breaths/min in the upper abdomen. [18]…”
Section: Discussionmentioning
confidence: 99%
“…[17] Another study evaluating the accuracy of a stretch sensor in measuring respiratory rate demonstrated differences between the site of measurement such as umbilicus, upper abdomen, xiphoid process and upper thorax with the largest error of 1.05 to −0.90 breaths/min in the upper abdomen. [18] A spirometer measures the airflow caused by breathing and is considered to be an accurate and reliable method of measuring respiration, with few artifacts caused by motion. [19] However, wearing it on the body or carrying around is not suitable, as is wearing a wearable device, and there is discomfort due to the need to continuously apply the mouthpiece during measurement.…”
Section: Sensing Site Positionmentioning
confidence: 99%
“…This integral remote monitoring philosophy was proposed by Goodbridge et al to further comprehend the outcomes of cost-effective systems in case-oriented environments since approximately 50% of the global population lives in rural or similar communities [55,56]. The protocol of this study was designed to lay the groundwork for future physiological research in real-world settings where the three postures are common in daily activities, while the deep breathing and supine scenarios can simulate the resting and sleeping states [29,57]. and IT experts.…”
Section: Remote Healthcare Monitoring In Rural Areas: Latin America A...mentioning
confidence: 99%
“…The chest movements during breathing produce changes of capacitance in the thorax cycle that can be measured using impedance measurement systems [ 8 , 9 , 10 ]. Other devices estimate the mechanical oscillations of the thorax during breathing using inertial sensors, strain gauges, inductance plethysmography, or flexible resistive bands [ 11 , 12 , 13 , 14 , 15 ]. In general, the systems are accurate and can perform breathing monitoring correctly.…”
Section: Introductionmentioning
confidence: 99%